Financial accounting and reporting fundamentals II : partnership and corporation - Frias, Solita A.; Fajardo, Consolacion L. (Manila : Unlimited Books Library Services & Publishing , Inc., 2019)
"This book is primarily designed as a textbook for accounting students who have completed the fundamentals of accounting for sole proprietorship and for service, trading and manufacturing businesses. There has been an urgent need for textbooks in partnership and corporation written within the framework of Philippine legal and tax requirements. To answer the need, the authors have written this book within such framework. The authors have incorporated partnership and corporation laws, Bureau of Internal Revenue (BIR) and Securities and Exchange Commission (SEC) rules and regulations."
Includes appendices.
English.
Keywords: Financial accounting; Accountancy